Governance reforms in public universities in Malaysia - Fauziah Md. Taib; Ng, Melissa Lee Yen Abdullah (Academic imprint series, 2015)
This book details the careful findings of the project entitled Governance Reforms in Malaysia Higher Education with Focus on Institutional Autonomy and Its Effects of University Governance and Management. As such, readers can look forward to gaining a thorough understanding of the reform measures taken in higher education governance and the extent of their impact. Four areas of autonomy are extensively covered: institutional, financial, academic and human resource autonomy. The challenges faced in the individual areas are painstakingly dissected and presented, leading up to projections and recommendations on the way forward in Malaysian higher education governance.